Moon Rocks - Cooper Henry S.F (The Dial Press, 1970)
Authors Note, Some Conclusions: Washington and September 15 - 1969, Previews: June 25-July 20 - 1969, On the Moon: July 20 - 1969, Preparations: July 20-July 1969, The First Rocks: July 24-July 25, P.E.T. Work I: July 26-August 10, P.E.T. Work II: August 10-September 30, Scattering: September 15-September 20, Interlude: Appolo 12 - October 28-December 5, The Moon in Houston: January 5-January 8 - 1970, Appendix.